2021
DOI: 10.3390/hemato2020019
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Immune Disorders Associated with Myelodysplastic Syndromes

Abstract: Systemic auto-inflammatory or autoimmune diseases (SIADs) develop in up to a quarter of patients with myelodysplastic syndromes (MDS) or chronic myelomonocytic leukemia (CMML). With or without the occurrence of SIADs, the distribution of MDS subtypes and the international or CMML-specific prognostic scoring systems have been similar between MDS/CMML patients. Moreover, various SIADs have been described in association with MDS, ranging from limited clinical manifestations to systemic diseases affecting multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 155 publications
(180 reference statements)
0
2
1
Order By: Relevance
“…MDS is associated with inflammatory complications [ 65 ], but despite this we did not find any significant association between pretransplant signs of inflammation and MDS/AML-MDS. This observation suggests that the risk of posttransplant acute GVHD/nonrelapse mortality associated with pretransplant inflammation [ 12 , 13 ] is similar for patients with and without MDS/MDS-AML.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…MDS is associated with inflammatory complications [ 65 ], but despite this we did not find any significant association between pretransplant signs of inflammation and MDS/AML-MDS. This observation suggests that the risk of posttransplant acute GVHD/nonrelapse mortality associated with pretransplant inflammation [ 12 , 13 ] is similar for patients with and without MDS/MDS-AML.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies, as well as a large meta-analysis, have shown that pretransplant signs of inflammation are associated with decreased survival and increased acute GVHD [ 12 , 13 ]; an increased early mortality for this group is therefore not unexpected. Furthermore, even though inflammatory/immune complications are increased among MDS patients [ 65 ], we could not detect any difference in CRP levels between the patients with MDS/MDS-AML and the other patients. The frequency of GVHD (together with the risk of relapse) is regarded as a major challenge in allotransplanted MDS patients [ 81 , 87 ], and recent studies suggest that intensified GVHD prophylaxis should be considered for MDS patients [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation